Ship Hydrostatics and Stability - Biran, Adrian; López-Pulido, Rubén (Elsevier : Butterworth-Heinemann, 2024)
Ship Hydrostatics and Stability, Third Edition, is a comprehensive guide to understanding ship hydrostatics in ship design and ship performance, taking you from first principles through basic and applied theory to contemporary mathematical techniques for ship design and project approval. Real-life examples are used to explain the theory and calculations using MATLAB and Excel. The new edition of this trusted resource covers new naval architecture regulations, such as a Second-Generation Intact Stability Code (SGISC), and new case studies. Extensive reference to computational techniques is made throughout, and downloadable MATLAB files accompany the book to support your own hydrostatics and stability calculations. The book also includes tables of notations and technical terms, as well as indexes in English, French, German, Italian, and Spanish.